USING MODERN METHODS OF FOREIGN LANGUAGE TEACHING AND APPLIED AT THE TYPES OF WAYS TO USE THEM EFFECTIVELY (Academia Science Repository, 2023)
In this article, the priorities of the modern teaching methodology of learning foreign languages, as well as the types of innovative methods and ways of their effective use, as well as recommendations on what to pay attention to in the development of speech, are given. In addition, these methods are analyzed using examples.